Efficacy of natural L-asparagine in the complex therapy for malignant tumors in experimental studies - Urazova, L.N.; Kuznetsova, T.I.; Boev, R.S.; Burkova, V.N. (Experimental Oncology, 2011)
Aim: To study the influence of natural L-asparagine on the efficacy of cytostatic therapy for malignant tumors in experimental investigations. Materials and Methods: Female C57B1/6 mice weighing 18–20 g were selected for the experiments. Lewis’ lung carcinoma (LLC) and melanoma B16 cells were used in the study. Animals were inoculated with tumor cells intramuscularly. Solution of L-asparagine in a volume of 0.2 ml per mouse (in appropriate doses) was administered to the animals using gastric probe, daily, for 14 days. Cyclophosphane was administered intraperitoneally in total doses of 180 mg/kg and 90 mg/kg on days 3 and 7 after tumor implantation. The percentage of tumor growth inhibition was calculated and inhibition index and frequency of metastasis were assessed. Results: It has been shown that despite low activity of L-asparagine with regard to primary tumor, the level of metastasis inhibition is rather high (up to 91% depending on experimental model, therapy regimen and follow-up period). The analysis of previously obtained data and our studies indicate that L-asparagine derived from burdock (Arctium lappa) root has not only its own antimetastatic activity but it is also able to increase antimetastatic activity of cyclophosphane partially reducing toxic effect of cyclophosphane on the organism without decreasing its antitumor and antimetastatic activities. Conclusion: L-asparagine derived from burdock (Arctium lappa) root can be effective in the complex anticancer therapy with the use of appropriate chemotherapy doses and regimens.